Cervical vertebral fracture: A report of two cases of “Near-Miss” C6 fractures - Ren, Yi Kow; Ab. Wahid, Hazwan; Jaya Kumar, Ruben; Mor Japar Khan, Ed Simor Khan; Komahen, Colin; Chooi, Leng Low (International Medical University, Malaysia, 2018)
Cervical spine injury is commonly associated with road-traffic accidents. The true incidence of cervical spine injuries is unknown due to under-reporting of such injuries. Cervical spine injury is associated with high morbidity and mortality if it is missed. With the advancement of imaging modalities, the number of missed cervical injuries has reduced. Nevertheless, some clinicians are dependent solely on imaging tools to rule out cervical spine injury in a trauma victim. We report two cases of a “near miss” C6 fracture to highlight the importance of a detailed clinical history and clinical examination with imaging as an adjunct to rule out cervical injury.